Epidemiologia e quadro clínico do botulismo epizoótico dos bovinos no Estado de São Paulo - Lisbôa, Julio Augusto N.; Kuchembuck, Marcio R. G.; Dutra, Iveraldo S.; Gonçalves, Roberto C.; Almeida, Clóvis T.; Barros Filho, Ivan R. (My University, 1996)
In order to investigate epidemiological and clinical aspects of beef cattle mortalities caused by botulism, a syndrome popularly known as doença da vaca caída, studies were carried out in 32 naturally affected 4 to 9 year old cows, 27 belonging to the Nellore breed and 5 to crossbred Nellore, all from 27 farms located in municipalities near Botucatu, State of São Paulo. The epidemiological and clinical features were based, respectively, on the farm and herd managements, and on the general physical examination of the cows. Mouse bioassay and complement microfixation tests were performed to detect the presence of botulinum toxins in liver samples. The results showed that the disease occurs in beef cattle of range breeding systems, reared under inadequate mineral nutrition and deficient health management. Pregnant and milking cows represented the group at risk, and the incidence was higher during the rainy season (December to March), with morbidity and mortality rates of 3,2 ± 3,6%. Clinical examination revealed cows with no alterations of vital signs, behavior, visual and auditory acuities and skin sensation; but revealed ruminal hypomotility, anorexia, dehydration, flaccid para or tetraparesis with permanent recumbency, and a paretic or paralytic tongue. The diagnosis of botulism, involving type C and D toxins, was consistent with the epidemiological and clinical findings.
Epidemiological and clinical aspects of the epizootic botulism of cattle in the State of São Paulo
Keywords: Cattle; Clinical signs; Epidemiology; Epizootic botulism